Comparative Study of Tweed Triangle in Angle Class II Division 1 Malocclusion between Nepalese and Chinese Students - Sharma, Bishnu Prasad; Xin, Chang; Sharma, Jagan Nath (Journal of Patan Academy of Health Sciences, 2015)
Introductions: The establishment of specific cephalometric norms for specific race or ethnic group has been documented in literatures. The aim of the present study was to compare the Tweed triangle for Nepalese and Chinese subjects with Angle Class II division 1 malocclusion. Methods: The cephalometric radiographs of 52 Nepalese and 52 Chinese students age between 14 to 18 years, Class II division 1 malocclusion with Point A-Nasion-Point B angle larger than 4 degrees were analyzed for 9 parameters. Results: Mean age of Nepalese participants was 14.28 years and that of Chinese 14.09. The comparative variables of Nepalese and Chinese population were: Y axis (61.39 and 67.52), Sella Nasion Point A angle (83.69 and 81.14), Sella Nasion Point B angle (76.87 and 74.62), Occlusal plane angle (19.0 and 23.12), Frankfort Mandibular plane angle (28.13 and 32.87) and Lower Incisior to Frankfort Horizontal plane Angle (54.77 and 48.23). Conclusions: The Class II skeletal pattern, well positioned maxillas and retrusive mandibles were present in both samples. The Chinese showed more protruded maxilla, more buccal inclination of lower incisors and longer face than Nepalese. Plain Language Summary: The study was done to identify the Tweed triangle for a sample of Nepalese and Chinese subjects with Angle Class II division 1 malocclusion . The study found that the both samples showed Class II skeletal pattern, well positioned maxillas and retrusive mandibles but the Chinese had more protruded maxilla, more buccal inclination of lower incisors and longer face than Nepalese. It showed the importance of ethnic role as Nepalese have distinct cephalometric features, which should be used as a reference while treating the Nepalese orthodontic patients. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13008 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):8-12